A Pre-Generation of Emergency Reference Plan Model of Public Health Emergencies with Case-Based Reasoning - Ru D; Wen H; Zhang Y (Dove Medical Press, 2022)
Danyang Ru, Haoyu Wen, Yuntao Zhang School of Economics and Management, Xidian University, Xi'an, Shaanxi, People's Republic of ChinaCorrespondence: Haoyu Wen, Email hywen@xidian.edu.cnBackground and Purpose: In the early 21st century, the coronavirus alone has ravaged the world three times. Public health emergencies have caused a tremendous negative impact on public health, daily life, and global economic development, for having the characteristics of complexity and great harm. To tackle these problems, a pre-generation of emergency reference plan model of public health emergencies is proposed to better deal with the outbreak and spread of public health events.Methods: The method is divided into three stages. First, the modified SEIR model is used to predict the attribute values of the target case. Then, the similar case sets are extracted and filtered by calculating the similarity through the cross-efficiency evaluation method with the parallel system. Finally, the multi-stage emergency effect evaluation model is conducted so that the emergency plan with the best response effect at this stage can be made for reference.Results: We collected 25 typical events of COVID-19 that occurred in 11 cities in China as historical case bases and target cases, respectively. The result of the experiment verified the feasibility and effectiveness of the proposed method.Conclusion: This paper presents a new perspective on making a public health emergency plan, which could improve the decision-making accuracy and efficiency, maximize the emergency effect and save precious time for emergency response. This model can provide rapid decision supports for decision-making for public services such as government departments, centers for disease control, medical emergency centers and transport authorities, etc.Keywords: public health emergencies, case-based reasoning, data envelopment analysis, modified SEIR model, life cycle model